Application of Carbon-Based Nanomaterials as Fertilizers in Soils - Bisinoti, Márcia Cristina; Moreira, Altair Benedito; Melo, Camila Almeida [UNESP]; Fregolente, Lais Gomes [UNESP]; Bento, Lucas Raimundo [UNESP]; Vitor dos Santos, João [UNESP]; Ferreira, Odair Pastor (Elsevier, 2019)
Nanomaterials produced from different carbonization methods and using different biomasses have been developed as fertilizers for soil. The preparation of nanomaterials through processes that use less chemical reagents and that are conducted under conditions closer to the environment that allow the use of residual biomasses will be highlighted. Due to the intrinsic physicochemical properties that nanomaterials present, they act toward improving the availability of nutrients in soil, in a controlled way, thus, minimizing environmental contamination as well as the use of chemical fertilizers, which is one of the guidelines for increasing food production efficiency. The regulation of the use of nanomaterials in soils and carbon sequestration are other aspects to be addressed. Thereby, this chapter shows how nanomaterials can be used as fertilizer, starting with an environment-friendly process for their production, to a safer application in the environment, reusing biomass residues, and adding value to them.
Keywords: Biomass; Carbon-based nanomaterials; Hydrothermal carbonization; Nutrients; Pyrolysis; Soil availability